The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1988
DOI: 10.1080/00039896.1988.9935856
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavioral Estimation of Children with Life-Long Increased Lead Exposure

Abstract: A battery of neurobehavioral examinations was carried out on 30 children who were 6-11 yr of age and who had resided near a lead smelter all their lives. Their blood lead levels were 35-60 micrograms/100 ml and erythrocyte protoporphyrin levels were greater than 100 micrograms/100 ml. Neurological examination revealed that they had a significantly higher incidence of pathological findings (e.g., muscle hypotonia, increased tendon reflexes, dysarthria, and dysdiadochokinesia) than children from an unpolluted ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…[3][4][5][6] A spectrum of neurocognitive and behavioral deficits in children have been attributed to Pb exposure, ranging from learning disabilities and mental retardation to antisocial behavior. [7][8][9][10][11][12] Our previous studies in highly Pb-contaminated Ecuadorian villages where Pbglazing of ceramics is the primary occupation have shown cases of extreme pediatric plumbism and associated neurocognitive impairment. 1,13 Although the Centers for Disease Control and Prevention (CDC) 14 has identified a pediatric blood lead (PbB) level of 10 g/dL (0.483 mol/L) as the risk management level, some investigators have reported adverse outcomes in tests of intellectual abilities in children with PbB levels below 10 g/dL.…”
mentioning
confidence: 99%
“…[3][4][5][6] A spectrum of neurocognitive and behavioral deficits in children have been attributed to Pb exposure, ranging from learning disabilities and mental retardation to antisocial behavior. [7][8][9][10][11][12] Our previous studies in highly Pb-contaminated Ecuadorian villages where Pbglazing of ceramics is the primary occupation have shown cases of extreme pediatric plumbism and associated neurocognitive impairment. 1,13 Although the Centers for Disease Control and Prevention (CDC) 14 has identified a pediatric blood lead (PbB) level of 10 g/dL (0.483 mol/L) as the risk management level, some investigators have reported adverse outcomes in tests of intellectual abilities in children with PbB levels below 10 g/dL.…”
mentioning
confidence: 99%
“…Some of these investigators reported results from inner city children who were exposed to low levels of environmental lead. Other studies were conducted on children residing at the lead smelter site (1). Because of close proximity to the lead sources, these children had high blood lead (PbB) burdens.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2 presents sway area response data from the patient and, for comparison, data from a nonexposed 14-year-old boy, a group of nonexposed 26-year-olds, and a group of lead-exposed children of about 5 years of age from other ongoing research projects.' [1][2][3][4][5][6][7][8][9][10][11][12] The patient performed all sway tests without falling. He did, however, show difficulty during tests of eyes open (FO) and closed (FC) standing on foam.…”
Section: Resultsmentioning
confidence: 99%